PROSPECTIVE SCIENCE TEACHERS’ REFLECTIONS ON THE USE OF LEARNING STRANDS IN DEVELOPING LESSON DESIGN - Shashi Prabha; Rakesh Kumar (European Scientific Journal, ESJ, 2014)
Learning strands as a framework seem to give an alternative to the fixed way of planning and provide the needed space to the students for constructing knowledge in a classroom. In order to facilitate process of teaching-learning of science in a more flexible paradigm, prospective teachers need to be convinced that developing lesson design is an open-ended activity and there should always be space for redesigning learning experiences by observing reactions and responses of students. This will help in catering to the learning needs of diverse human potentials in classroom. In the present study, an attempt has been made to study reflections of the prospective teachers on the use of learning strands in developing lesson design in a more flexible paradigm. It is concluded that use of learning strands in developing lesson design can substitute specific objectives used in traditional form of lesson plan where rigid adherence of the processes of teaching learning with pre-conceived notions is emphasized. Teacher educators might look at the lesson planning framework in the light of using learning strands in the development of lesson design.